2017
DOI: 10.1186/s40337-017-0179-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between interpersonal problems and treatment outcome in patients with eating disorders

Abstract: BackgroundInterpersonal problems are thought to play an essential role in the development and maintenance of eating disorders. The aim of the current study was to investigate whether a specific interpersonal profile could be identified in a group of patients diagnosed with Bulimia Nervosa, Binge Eating Disorder, or Eating Disorders Not Otherwise Specified, and to explore if specific types of interpersonal problems were systematically related to treatment outcome in this group of patients.MethodsThe participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
3
21
0
1
Order By: Relevance
“…Interpersonal problems have also been found to be present in even mild cases of depression (McFarquhar et al, 2018) and have been cited as prognostic and maintenance factors for eating disorders. Similarly, Ung et al (2017) found that eating-disordered patients display a nonassertive and friendly submissive interpersonal style, independent of specific eating disorder diagnosis. Similarly, Ung et al (2017) found that eating-disordered patients display a nonassertive and friendly submissive interpersonal style, independent of specific eating disorder diagnosis.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Interpersonal problems have also been found to be present in even mild cases of depression (McFarquhar et al, 2018) and have been cited as prognostic and maintenance factors for eating disorders. Similarly, Ung et al (2017) found that eating-disordered patients display a nonassertive and friendly submissive interpersonal style, independent of specific eating disorder diagnosis. Similarly, Ung et al (2017) found that eating-disordered patients display a nonassertive and friendly submissive interpersonal style, independent of specific eating disorder diagnosis.…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, interpersonal submissiveness is associated with treatment adherence in binge eating disorder, whereas reductions in binge eating symptoms predict increases in interpersonal dominance (Luo et al, 2018). Similarly, Ung et al (2017) found that eating-disordered patients display a nonassertive and friendly submissive interpersonal style, independent of specific eating disorder diagnosis. In terms of Axis II psychopathology, interpersonal problems are common as well (Joyce et al, 2017).…”
mentioning
confidence: 90%
See 3 more Smart Citations